The Effect of ICD Programming on Inappropriate and Appropriate ICD Therapies in Ischemic and Nonischemic Cardiomyopathy: The MADIT‐RIT Trial. (11th February 2015) - SEDLÁČEK, KAMIL; RUWALD, ANNE‐CHRISTINE; KUTYIFA, VALENTINA; MCNITT, SCOTT; THOMSEN, POUL ERIK BLOCH; KLEIN, HELMUT; STOCKBURGER, MARTIN; WICHTERLE, DAN; MERKELY, BELA; DE LA CONCHA, JOAQUIN FERNANDEZ; SWISSA, MOSHE; ZAREBA, WOJCIECH; et al.
ICD Programming in Ischemic and Nonischemic Cardiomyopathy Introduction The MADIT‐RIT trial demonstrated reduction of inappropriate and appropriate ICD therapies and mortality by high‐rate cut‐off and 60‐second‐delayed VT therapy ICD programming in patients with a primary prophylactic ICD indication. The aim of this analysis was to study effects of MADIT‐RIT ICD programming in patients with ischemic and nonischemic cardiomyopathy. Methods and Results First and total occurrences of both inappropriate and appropriate ICD therapies were analyzed by multivariate Cox models in 791 (53%) patients with ischemic and 707 (47%) patients with nonischemic cardiomyopathy. Patients with ischemic and nonischemic cardiomyopathy had similar incidence of first inappropriate (9% and 11%, P = 0.21) and first appropriate ICD therapy (11.6% and 14.1%, P = 0.15). Patients with ischemic cardiomyopathy had higher mortality rate (6.1% vs. 3.3%, P = 0.01). MADIT‐RIT high‐rate cut‐off (arm B) and delayed VT therapy ICD programming (arm C) compared with conventional (arm A) ICD programming were associated with a significant risk reduction of first inappropriate and appropriate ICD therapy in patients with ischemic and nonischemic cardiomyopathy (HR range 0.11–0.34, P < 0.001 for all comparisons). Occurrence of total inappropriate and appropriate ICD therapies was significantly reduced by high‐rate cut‐off ICD programming and delayed VT therapy ICD programming in both ischemic and nonischemic cardiomyopathy patients. Conclusion High‐rate cut‐off and delayed VT therapy ICD programming are associated with significant reduction in first and total inappropriate and appropriate ICD therapy in patients with ischemic and nonischemic cardiomyopathy.